Specific characteristics and challenges associated with breast cancer diagnostics in women after breast augmentation and reconstructive surgeries with implants - O. S. Khodorovich; V. A. Solodkiy; T. V. Sherstneva; L. B. Kanakhina; Sh. M. Dibirova (ABV-press, 2024)
Background. The number of plastic surgeries is constantly growing worldwide. Breast augmentation remains the most common surgical procedure in women, which demonstrated a 0.5 % increase over the past 4 years. As the number of women with breast implants increases, specialists and patients themselves face difficulties related to screening, diagnosis, and treatment of tumors, including breast cancer.Aim. To analyze specific characteristics of breast examination in patients after breast augmentation who were examined and treated in the mammological clinic of Russian Research Center of Radiology, Ministry of Health of the Russian Federation.Materials and methods. This study included 273 patients aged between 21 and 63 years (mean age 49.0 ± 7.6 years) after breast augmentation and after reconstructive surgery for breast cancer and symmetrizing surgery on the contralateral side. All women underwent clinical examination plus breast ultrasound (for patients under 40 years of age) or mammography followed by ultrasound (patients over 40 years of age). Patients who were found to have BI-RADS 3-4 tumors underwent ultrasound-guided or stereotactic breast biopsy. In case of suspicious intraductal formations according to breast nipple smears the patients were referred to breast ductography. Patients with suspected implant rupture or capsular contracture, as well as patients requiring the assessment of the disease stage underwent contrast-enhanced magnetic resonance imaging.Results. After comprehensive examination, 12 patients (5.4 %) were diagnosed with breast cancer; 38 patients (13.9 %), with implant rupture; 3 patients (1 %), with intraductal formations.Conclusion. Breast augmentation is not a contraindication to mammography in women aged over 40 years with glandular tissue. Additional examination methods include breast ultrasound, contrast-enhanced mammography, and breast magnetic resonance imaging. In case of no glandular tissue, contrast-enhanced breast magnetic resonance imaging and breast ultrasound are the methods of choice. It is important to develop new standards of screening and diagnosis of breast diseases in women after aesthetic surgery, since breast cancer incidence is likely to increase among women after breast augmentation over the next decades, considering the fact that breast cancer is the most common malignancy in women and its incidence is constantly growing.